Karakteristik Azolla pinnata sebagai Pengganti Bahan Pembawa Pupuk Hayati Padat Bakteri Penambat N2 dan Bakteri Pelarut P - Mieke Rochimi Setiawati; Pujawati Suryatmana; Amalia Chusnul (Fakultas Pertanian Universitas Padjadjaran, 2017)
The use of inorganic fertilizers for a long term can reduce soil fertility. One of the alternatives solving this problem is by using solid biofertilizers. Solid biofertilizer requires carrier materials that can support the viability of potential microbial within. Azolla pinnata is one of the carriers that has potential as a substitute for commonly used carrier materials. This study aims to determine the effect of Azolla pinnata and other organic materials with inoculant dosage on viability of bacterial population, N-total, P-total of solid biofertilizer. This research was conducted at Soil Biology Laboratory, Department of Soil Science, Faculty of Agriculture, Padjadjaran University in January-February 2015. The treatments were organic matter (Azolla pinnata, litter compost and peat) with various dosages of bacterial inoculant (20%, 25% 30%). This experiment used the Completely Random Design with factorial pattern. The main observations of the study were analyzed by ANOVA test and continued with Duncan test with 5% confidence level. The results showed that Azolla pinnata carrier has significantly effect to the increase of N-Total and P total of solid biofertilizer. The inoculant dosage of 30% affects the population increase of Azotobacter sp., and endophytic bacteria, but does not effect to the population of Phosphate Solubilizing Bacteria and Azospirillum sp. Azolla pinnata can be recommended as an alternative carrier that can replace peat and litter compost materials.The results of this study was illustrate Azolla pinnata can be recommended as an alternative carrier for solid biofertilizer that can replace peat and litter compost material with 30% inoculant dosage.Keywords: Azolla pinnata compost, litter, peat, solid biofertilizer